Երեխաների նկատմամբ բռնության հիմնախնդրի պատմական ակնարկ - Աննա Օվչյան (ՀՀ ԳԱԱ հրատ.)
Thus, violence and cruel-treatment towards children has always been a specific historical phenomenon, caused by economic and socio-cultural circumstances.The society gradually realize that violence towards children, cruel-treatment and neglect of basic needs as a social problem.
Keywords: Philosophy; Psychology; Religion; Psychology